Thursday

February 26, 2015

February 26, 2015

Posted by **4611star** on Sunday, February 19, 2012 at 10:15am.

2 2 2 2

(n-1) + n + (n+1) = 3n +2

- maths -
**Reiny**, Sunday, February 19, 2012 at 10:31amYour statement

(n-1) + n + (n+1) = 3n +2

is false

(n-1) + n + (n+1)

= n-1+n+n+1

= 3n

I dont know what 2 2 2 2 is supposed to mean.

- maths -
**Steve**, Sunday, February 19, 2012 at 11:44amLooks like an attempt at exponents, not counting on html formatting:

(n-1)^2 + n^2 + (n+1)^2 = 3n^2 + 2

Now come on, guy. Just expand the expressions, and the +2n and -2n cancel out, and the +1 and +1 add up to 2.

Where do you have trouble here?

**Answer this Question**

**Related Questions**

maths - If the sum of the squares of the roots of the quadratic equation ax^2 + ...

Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...

Advanced Maths (Vectors) AQA Level - Triangle ABC with D, E and F the midpoints ...

DISCRETE MATHS - Prove that for every set S, Ø \subseteq( S. i need to Use ...

Maths - X and Y are points on the sides BC and AC of a triangle ABC respectively...

Maths - prove that 2+2=5

maths - prove that: 1/1+x^b-a + x^c-a + 1/1+x^a-b +x^a-c = 1

maths - prove that : 2^n + 2^n-1 / 2^n+1 - 2^n = 3/2

maths - If a+b+c=0 then prove that a^4+b^4+c^4=2(a^2b^2+b^2c^2+c^2a^2)

maths - if x=1/(2-3^1/2) prove that x^3-2x^2-7x+5=3